Art and copyright - Llm, Simon Stokes (London, England : Hart Publishing, 2021)
"Revised and updated, this third edition includes additional coverage of the following topics: the relationship between designs law and artistic works; EU and Brexit developments; AI-created works; graffiti and other non-conventional works; blockchain and rights management; orphan works; new exceptions to copyright; digital copyright, art databases and online platforms"
The copyright system : justification and history -- The modern law of copyright -- Moral rights and artist's resale right (droit de suite) -- Art, technology and the internet : copyright, related rights and digitisation -- Some current issues -- Some practical issues and precedents -- Art and intellectual property rights other than copyright.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Copyright -- Art -- Great Britain; Internet -- Law and legislation -- Great Britain; Copyright -- Art; Internet -- Droit -- Grande-Bretagne.; Droit d'auteur et informatique -- Grande-Bretagne.; Intellectual property law,Copyright law; Electronic books